Does Disproportionate Financial Inclusion Reduce Gender and Income-Group Inequality? Global Evidence - Soon Suk Yoon; Ingyu Oh; Shawn S. Park (International Journal of Financial Studies, 2025)
This paper investigates whether countries’ investments in financial inclusion, beyond what their economic capacity would predict, help mitigate gender and income-group gaps in financial opportunities. We construct a novel index, the Abnormal Financial Inclusion Index (AbFII), as the residuals from a regression of financial inclusion on GDP per capita to isolate country-specific efforts in advancing financial inclusion. Using data from 100 countries between 2014 and 2021, we find that higher AbFII is associated with lower gender and rich-poor inequalities in financial inclusion, particularly in low-income and high-inequality countries. A one-standard-deviation increase in AbFII corresponds to a 1.2 percentage point reduction in gender and income-group disparities in financial access. We also find that AbFII predicts subsequent improvements in broader gender inequality, especially in reproductive health. The results are robust to various controls and remain consistent under instrumental variable analysis using broadband penetration as an instrument. Our findings suggest that financial inclusion policies exceeding the level expected by economic development can significantly reduce social disparities.